Superior-subordinate communication dimensions and working relationship: Gender preferences in a Malaysian organization - Abu Bakar, Hassan; Mohamad, Bahtiar; Mustaffa, Che Su (Routledge, 2007)
This paper attempts to investigate the Western proposition on the communication preferences of male and female employees in a Malaysian organization. Based on the literature, Western scholars suggest that male employees prefer working communication with their superior that will allow them to accomplish their jobs. On the other hand, female employees prefer relationship communication with their superior in order to maintain and develop their relationship with their superior. Our findings show the combination's of working and relationship communication emerging from Malaysian male and female respondents. The consequences of these findings are discussed and elaborated.